1998
DOI: 10.1111/j.1749-6632.1998.tb10655.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral Replication in Olfactory Receptor Neurons and Entry into the Olfactory Bulb and Braina

Abstract: This communication describes our ongoing studies of the interaction of the mouse host and vesicular stomatitis virus (VSV). When VSV is applied to the nasal neuroepithelium, it initially replicates in olfactory receptor neurons, and is transmitted along the olfactory nerve to the central nervous system (CNS) within 12 hours. In the olfactory bulb, the virus replicates invasively through the layers of the olfactory bulb, reaching the olfactory ventricle by day 4-5 post infection, and the hindbrain by day 8 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
91
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 25 publications
2
91
0
Order By: Relevance
“…Because virus could not be reisolated from surviving mice, these results proved clearance of virus in the brains of the surviving mice (9). Thus far, it is unclear how exactly virus clearance is accomplished within the brain.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Because virus could not be reisolated from surviving mice, these results proved clearance of virus in the brains of the surviving mice (9). Thus far, it is unclear how exactly virus clearance is accomplished within the brain.…”
Section: Discussionmentioning
confidence: 84%
“…high-dose infection of WT mice, VSV can be detected in brains of virtually all infected animals, whereas only 50% of the animals eventually died, indicated that virus infection was controlled within the CNS (9). Although administration of high-dose IFN after i.n.…”
mentioning
confidence: 99%
See 3 more Smart Citations